Effect of humidity on the interaction of CO2 with alkaline anion exchange membranes probed using the quartz crystal microbalance. (21st September 2017) - Bharath, V.J.; Jervis, J.R.; Bailey, J.J.; Engebretsen, E.; Neville, T.P.; Millichamp, J.; Mason, T.; Shearing, P.R.; Brown, R.J.C.; Manos, G.; Brett, D.J.L.
Abstract: The alkaline anion exchange membrane fuel cell (AAEM-FC) is able to deliver a comparable performance to the traditional proton exchange membrane fuel cell (PEM-FC) without the use of precious metal electrocatalysts, making it a more cost-competitive alternative for low-temperature fuel cell applications. However, issues relating to degradation and specifically interaction with CO2 still hinder the technology's commercialisation prospects. With hydration playing a key role in solid polymer electrolyte fuel cell operation, this study examines how membrane hydration affects the AAEM interaction with CO2 . The change of membrane conductivity upon exposure to atmospheric CO2 has been compared with the change in viscoelastic properties of a cast thin-film ionomer, both as a function of humidity. The effect of CO2 on the membrane as a function of hydration suggests a link to its solvation and swelling regimes and thus the access of CO2 to the ionic channels within the membrane. The thin-film QCM composite resonator study has suggested that during the solvation (pore opening) regime, there is a linear increase in CO2 uptake as water can further permeate the pore system and the cationic headgroups become increasingly accessible. During the transition to the pore swelling regime, there is a step increase in CO2 uptake as the network is thought to be fully open; as such, subsequent increases in RH do not lead to any significant increase in CO2 uptake. Highlights: Membrane hydration shown to affect AAEM interaction with CO2 . Hydration shows greater shifts in membrane resistance for operation in air. Pore opening and pore swelling have different regimes of CO2 interaction. Opening of membrane pore network leads to increasing CO2 uptake.